GENERAL ITERATIVE METHODS FOR A FAMILY OF NONEXPANSIVE MAPPINGS - Yazdi, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper, we introduce implicit and explicit iterative methods for finding a common element of the set of solutions of a variational inequality and the set of common fixed points for a countable family of nonexpansive mappings in a Hilbert space. For these methods, we prove some strong convergence theorems. These theorems improve and extend some results of Yao et al. [21] and Xu [20].